The water quality study and sources of pollution in Alur Ilmu, UKM [Kajian kualiti air dan punca-punca pencemaran di Alur Ilmu, UKM] - Nurul Afina, Abd Mutalib; Ahmad Dasuki, Mustafa; Othman, A. Karim (Malaysian Society of Analytical Sciences, 2015)
The Alur Ilmu UKM is a large storm water channel that serves to store water and flows into Langat River. The primary objective of this study are to identify the water quality and pollution levels, the sources of which may cause pollution and to measures the control pollution that occurs in the area. Water sampling was carried out in order to determine the quality of water. The sampling water was taken during no-rain and after rainfall. The area includes UKM Forest Reserve (Hutan Pendidikan Alam – HPA), Student Cafeteria (Teres Eko Niaga), Restaurant of Fakulti Sains dan Teknologi (FST), Student Centre (Pusanika), Fakulti Pendidikan Islam (FPI) and UKM Mosque. Eight water quality parameters i.e consisting of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Turbidity, Total Suspended Solids (TSS), Total Kjeldahl Nitrogen (TKN), Temperature, Oil and Grease (O&G) were measured. The results shows that the water quality are in a class III and IV according to Water quality Index (WQI) and the water meet the standard B that set out in the Regulations of the Environmental Quality (Sewage and Effluent).